P545 Does gender matter? Gender-related nutritional behaviour, disease activity and quality of life in patients with inflammatory bowel diseases. (30th January 2023) - Pueschel, L; Kockelmann, F; Kueck, M; Tegtbur, U; Seidler, U; Lenzen, H; Attaran-Bandarabadi, M; Bachmann, O; Wedemeyer, H; Wiestler, M
Abstract: Background: The latest research clearly indicates that diet plays an important role in the onset and course of inflammatory bowel diseases (IBD). But especially data on gender specific aspects of diet in IBD patients are still lacking even though we know from the general population that gender matters in case of diet. Methods: We hypothesised an interaction of gender and diet in IBD patients and that this is linked to disease behaviour. In a subgroup analysis of a previously published prospective trial (Wiestler M. et al., Clinical and Translational Gastroenterology, 2019) 91 IBD patients were stratified into 4 groups (Crohn's disease - CD [n=50] and ulcerative colitis – UC [n=41], female and male, respectively) to compare nutritional behaviour by sex and diagnosis. We evaluated disease-specific quality of life (IBDQ), physical activity (accelerometery), body composition (bioelectrical impedance analysis (BIA)), as well as clinical (HBI, SCCAI) and biochemical (CRP, faecal calprotectin) parameters of disease activity in comparison to nutritional behaviour (food frequency questionnaire (FFQ)). Results: The nutritional behaviour of CD patients showed significant gender-related trends and differences in correlation with disease activity (Spearman correlation analysis). In male CD patients HBI significantly negatively correlated with the amount of fish (p=0.005, r=-0.612) and meat consumed per month (p=0.023, r=-0.519). In female CD patients the amount of fish consumed per month significantly negatively correlated with the IBDQ score (p=0.029, r=-0.438). The nutritional behaviour of UC patients showed significant gender-related trends and differences in correlation with disease activity as well. In female patients SCCAI significantly negatively correlated with the amount of cake, pie/ sweet baked goods (p=<0.001, r=-0.832) and significantly positively correlated with the amount of poultry consumed per month (p=0.006, r=0.715). Furthermore, in female patients the amount of pizza consumed per month significantly positively correlated with the IBDQ score, subscore social (p=0.016, r=0.653). Conclusion: In this subgroup analysis of a cross-sectional study, nutritional behaviour of IBD patients showed significant gender-related differences in correlation with disease activity and disease related quality of life. Due to the close correlation between IBD and nutrition and the different nutritional needs according to disease activity, our results illustrate the importance of gender-sensitive collection of a nutritional history as well as the need for gender-sensitive nutritional recommendations in IBD patients to further optimize individual patient care.